2011
DOI: 10.1016/j.otsr.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Primary total knee arthroplasty in the management of epiphyseal fracture around the knee

Abstract: IV; retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 29 publications
3
67
0
4
Order By: Relevance
“…The same bias of including distal femoral fractures was noted in another study. 29 Comparable results were published by Vermeire and Scheerlinck 6 and Haufe et al 28 Vermeire and Scheerlinck 6 reported an average KSS of 78 (range, 50-100), function score of 58 (range, 0-100), and excellent results in 7/12 (58%) in 12 patients. They claimed that the fair and poor results (four patients) were related to the poor general condition of those patients not to the procedure.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The same bias of including distal femoral fractures was noted in another study. 29 Comparable results were published by Vermeire and Scheerlinck 6 and Haufe et al 28 Vermeire and Scheerlinck 6 reported an average KSS of 78 (range, 50-100), function score of 58 (range, 0-100), and excellent results in 7/12 (58%) in 12 patients. They claimed that the fair and poor results (four patients) were related to the poor general condition of those patients not to the procedure.…”
Section: Discussionmentioning
confidence: 58%
“…Other authors highlighted similar conclusions recommending primary TKA for acute geriatric tibial plateau fractures. 6,[28][29][30][31][32][33] The length of hospital stay (LOS) was similar in both groups averaging 12.5 days in TKA patients and 10.4 days in ORIF patients. This is mainly because of the emergency nature of the procedure and the associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors described 23 % of immediate general complications and 15 % of local knee-related complications. With these data they concluded that TKA is a suitable option for complex distal femoral or proximal tibial fracture in elderly patients, but the complication rate is higher compared to elective TKA and comparable to TKA in post-traumatic arthritis [ 14 ].…”
Section: Resultsmentioning
confidence: 97%